Optimizing mass rearing and field release of Telenomus remus for effective biological control of Spodoptera litura - De-Rui Han; Guang Zou; Chao-Zhou Liu; Xia Wen; Xiao-Fei Yu; Mao-Fa Yang; Guy Smagghe; Jian-Feng Liu; Chun-Yang Huang (Crop Protection, 2026)

Experimental study on mechanical properties of double-layer damped liquid storage tanks with various isolation devices - Xiang Li; Lei Xu; Fa Yang; Li-jie Zhu; Bo-lin Wang; Zheng Lu (Soil Dynamics and Earthquake Engineering, 2026)

Complementary vertical sensitivity unlocks full-column thermodynamics from combined ground and space microwave observations - Disong Fu; Qinghui Sun; Fa Tao; Xiangao Xia; Yunjie Xia; Zijue Song; Dazhi Yang; Hongrong Shi; Jiajia Mao; Ziqiang Zhu; Peng Zhang (Atmospheric Research, 2026)

In-situ phase transformation induced carboxyl protection boosts stability and activity of bismuth-based photocatalysts for CO2 reduction - Jiehao Li; Ying Liu; Shuoqing Qi; Biao Wu; Yi-lei Li; Jun Yang; Qian Wang; Ying-juan Hao; Fa-tang Li (Journal of Environmental Chemical Engineering, 2026)

Multi-site Ag-π conductive gel for ultrasensitive digital acousto-optic sensor - Jintao Tian; Yihao He; Hao-Ran Yang; Xing Han; Xiao-Wen Sun; Hong Yao; Tai-Bao Wei; Jin-Fa Chen; Bingbing Shi; Qi Lin (Chemical Engineering Journal, 2026)

Asymmetric coordination configuration unlocks single-atom nanozyme catalytic activity for redox-immune homeostasis and temporomandibular joint osteoarthritis therapy via macrophage depolarization and cGAS-STING pathway inhibition - Kaixun He; Hanyu Lin; Penghui Wei; Hongjia Zheng; Zhonghan Chen; Sihui Zhang; Yanjing Ou; Wenting Jiang; Wenxiu Yuan; Geyuan Zheng; Jiang Chen; Yi Zuo; et al. (Chemical Engineering Journal, 2026)

S-methoprene affected the population growth of Ephestia elutella (Hübner) - Lin-chong An; Xiao-fei Yu; Si-qi Wan; Mao-fa Yang (Journal of Stored Products Research, 2026)

Automatic detection of rocks on permanently shadowed regions (PSRs) of the Moon using PSR-BoulderNet - Yang Liu; Wenzhe Fa (Icarus, 2026)

Regulation mechanism of N2O and CH4 emissions during the pig manure composting amended with Polygonum Multiflorum Thunb - Ya-jun Duan; Hong-sheng Wu; Jiang-yu Yang; Zheng-tong Zhou; Tao-ran Shi; Cheng Cheng; Zhen-wei Li; Chun-fa Wu; Ming-chun Di; Yu-dong He; Feng-yi Hu (World Journal of Microbiology and Biotechnology, 2026)

Composite beeswax-glycerol monolaurate oleogelation enhances encapsulation efficiency and oxidative stability of microencapsulated Antarctic krill oil - Xin Sun; Liang Song; Rui-Ying Wang; Xin-Yang Ha; Fa-Wen Yin; Lei Qin; Bei-Wei Zhu; Da-Yong Zhou (Food Research International, 2026)

Chlorpyrifos exposure induced cytotoxic death in pancreatic islet β-cells via the functional co-activation of JNK and AMPKα signaling downstream-mediated mitochondria-dependent apoptosis pathway - Ching-Yao Yang; Kuan-I Lee; Ya-Wen Chen; Shing-Hwa Liu; Kai-Min Fang; Chun-Ying Kuo; Wei-Cheng Lia; Kai-Chih Chang; Jun-An Ke; Cheng-Tien Wu; Chun-Fa Huang; Chin-Chuan Su (Food and Chemical Toxicology, 2026)

Experimental study on the seismic performance and design optimization of precast piers with various connection types - Xinlei Yang; Xiang Li; Fa Yang; Quanchang Ren; Jianbao Miao; Yantao Liu; Yukai Zhang; Qingtao Zheng (Bulletin of Earthquake Engineering, 2026)

Enhanced wastewater treatment performance in a two-stage pyrite-based denitrifying deep bed filter - Jun Ding; Feng Ling; Shu-Yang Tian; Wen-Bo Xie; Xiao-Cai Chen; Li Yu; Xu-Mei Li; Fa-Zhi Xie; Wei-Hua Li; Tong-Zhan Xue; Hou-Yun Yang; Xian-Huai Huang (Journal of Environmental Chemical Engineering, 2026)

Effects of host density and instar stage on mass-rearing efficiency of Microplitis manilae (Hymenoptera: Braconidae) - Xiang-Qin Bai; Shuang Tian; Xue-Yuan Di; Hui-Zi Wu; Bin Yan; Peng Ren; Xiang-Yu Ji; Mao-Fa Yang (Journal of Asia-Pacific Entomology, 2026)

ICE1 plays a vital role in the development of pollen grains through regulating tapetum degradation and nutrient mobilization in Arabidopsis thaliana - Fa-Li Chang; Jer-Lun Kuo; Meng-Ting Wu; Ching-Hsing Liang; Shiang-Jiuun Chen; Chien-Chih Yang (Plant Molecular Biology, 2026)

Host preference and parasitism performance of two Habrobracon hebetor populations on three pyralid hosts: Implications for stored-product biocontrol - Hou-Ding Ou; Zhong-Jiu Xiao; Xun-Feng Peng; Mao-Fa Yang; Xiu-Qin Wang (Journal of Stored Products Research, 2026)

Layer-tuned polypropylene mesh as a cost-effective diaphragm for stable and high-efficiency electrochemical hardness removal - Meng-Meng Wang; Xiao-Yang Luo; Fa-Guo Chong; Peng-Jun Fan; Chao Zhang; Guang-Ping Zha; Wen-Fang Cai; Qing-Yun Chen; Yun-Hai Wang (Desalination, 2026)

Prediction and application of water inrush in water-rich area of TBM construction deep buried tunnel - Fa-yong Gao; Kun Yang; Yan-qiang Cheng; Yong-tao Ma; Kang Fu; Ming-yang Tang; Jin-rui Duan (Applied Geophysics, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

Amorphous phosphate-mediated Schottky junction at Mo2N-based heterojunction interface to accelerate interfacial electron transfer for boosted photocatalytic hydrogen evolution - Yu-pei Li; Zi-xin Qi; Xiao-jing Wang; Jun Zhao; Jun Yang; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2026)

Effects of a multigenerational exposure to graphene oxide on the growth, development, and reproduction of green peach aphids, Myzus persicae - Jie Fan; Syed Husne Mobarak; Mao-Fa Yang; Tong-Xian Liu; Chao-Xing Hu (Journal of Pest Science, 2026)

Inhibiting browning in ready-to-eat oysters: The efficacy and mechanism of L-cysteine combined with light-proof nitrogen-filled packaging during accelerated storage - Ying Luo; Jie Xu; Shuo Lv; De-Yang Li; Yuan-Yuan Hu; Xiao-Yang Liu; Fa-Wen Yin; Da-Yong Zhou (Food Research International, 2026)

Genome-wide association study of alkali tolerance at germination stage in wheat - Haoran Gu; Zixu Wang; Xiaotong Liu; Haotian Cao; Zixin Zhou; Meishan Zhou; Xinzhi Yang; Han Sun; Ran Qin; Chunhua Zhao; Yongzhen Wu; Fa Cui (Theoretical and Applied Genetics, 2026)

Integrative approaches to river ecosystem assessment and restoration: a review of methodologies and strategies for coherent implementation - Xian-bing Zhang; Shang Huang; Yu-peng Hu; Geng Li; Wen-jie Li; Sheng-fa Yang (Environmental Monitoring and Assessment, 2026)

Pioglitazone (PIO) enhances blastocyst vitrification outcomes via coordinated AQP3-mediated dehydration and antioxidant defense - Kai-Yan Zhang; Cai-Yu Wang; Jing Guo; Chang-Guo Min; Jun Wang; Jing Zhao; Yi Fang; Hong-Yu Liu; He Ding; Yang Lyu; Dian Wang; Xin Ma; et al. (Theriogenology, 2026)

Tracking seasonal variability in plant traits from spaceborne PRISMA and NEON AOP across forest types and ecoregions - Fujiang Ji; Ting Zheng; Alexey N. Shiklomanov; Ruqi Yang; Philip A. Townsend; Fa Li; Dalei Hao; Hamid Dashti; Kyle R. Kovach; Hangkai You; Junxiong Zhou; Min Chen (Remote Sensing of Environment, 2026)

Effects of a forage-native multi-PGPM consortium symbiotic system on rhizosphere ecology and microbial regulation for remediating PAHs-contaminated very-high-altitude coal mines - Deyu Dong; Zhanling Xie; Bao Wang; Weiyou Ou; Yongpeng Tang; Jiabao Yang; Yuting Guo; Xueting Fa (Journal of Hazardous Materials, 2026)

Toward noise-resilient retrieval of land surface temperature and emissivity using airborne thermal infrared hyperspectral imagery - Du Wang; Li-Qin Cao; Yu-Hao Du; Hai-Yang Xiong; Fa-Wang Ye; Yan-Fei Zhong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Study on browning mechanism of Antarctic krill meal during storage: based on the model system approach - Chao Guo; Xiang-Bo Zeng; Chang-Qiang Leng; De-Yang Li; Qian Wang; Fa-Wen Yin; Bei-Wei Zhu; Da-Yong Zhou (Food Chemistry, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Ophiocordyceps polystromata , a new entomopathogenic fungus from the Gaoligong Mountains in western Yunnan, China - He-Fa Liao; Ping-Ping Su; Ze-Mei Chen; Luo-Dong Huang; Qi Fan; Qiu-Lu Yang; Zhu-Liang Yang; Wei-Hong Hu; Yuan-Bing Wang (New Zealand Journal of Botany, 2025)

Population structure of Tachypleus tridentatus in Xiamen Bay: Proposing a network of transboundary marine protected areas - Yi-Hua Jin; Yi-Jia Shih; Hsin-I. Lin; Ya-Hui Chen; Yung-Sheng Cheng; Chia-Fa Lee; Yang-Chi Chang; Yi Chang (Regional Studies in Marine Science, 2025)

Multi-side-port nanotube array based on pillar[5]arene-Ag(I) self-assembly for efficient and recyclable separation of trace pyridine - Hao-Ran Yang; Jintao Tian; Xing Han; Tai-Bao Wei; Hong Yao; Bingbing Shi; Jin-Fa Chen; Qi Lin (Chemical Engineering Journal, 2025)

Theaflavin 3,3′-digallate suppresses metastasis and reduces insulin-like growth factor-1-induced cancer stemness and invasiveness in human melanoma cells - Ju-Pi Li; Yi-Hsien Hsieh; Yi-Hsun Lee; Wen-Yi Tsai; Shun-Fa Yang; Yih-Shou Hsieh; Pei-Ni Chen (Chemico-Biological Interactions, 2025)

Disruption of the SIRT1/PI3K/AKT Signaling Axis Mediates Fluoride-Induced Cardiotoxicity: Evidence from in Vitro and Zebrafish Models - Lei Guo; Bo Yang; Fa Chen; Xiaoshuang Yuan; Jinyang Cheng; Xiaoxu Chen; Ying Zhou; Xu Yang; Yanju Li; Yang Liu; Dongxin Tang; Feiqing Wang (Biological Trace Element Research, 2025)

Antimony induces mitochondria-dependent and ER stress-triggered apoptosis via the oxidative stress-activated JNK signaling pathway in pancreatic islet β-cells - Ken-An Lin; Chin-Chuan Su; Shing-Hwa Liu; Kuan-I. Lee; Kai-Min Fang; Chih-Hsin Tang; Chun-Ying Kuo; Kai-Chih Chang; Jun-An Ke; Chun-Fa Huang; Ya-Wen Chen; Ching-Yao Yang (Toxicology, 2025)

Aggregation pheromones of Bostrichidae: A review - Li Yu; Xiao-Lu Cao; Wei Zheng; Jun Li; Fa-Yang Xie; Xia-Lin Zheng (Journal of Stored Products Research, 2025)

Investigation on the influence of droplets on the flow characteristics and energy separation in vortex tube based on CFD analysis - Lijuan He; Zhong Zhou; Zhi Li; Jianzi Yang; Fa Zhang; Xingyu Meng; Wenxi You; Chenlei Zhao (International Journal of Refrigeration, 2025)

Sensory characteristics and key odor-active compounds of oxidized Antarctic krill oil: A comparative study with oxidized fish oil - Gui-Mei Dong; Rui-Ying Wang; Fa-Wen Yin; De-Yang Li; Lei Qin; Da-Yong Zhou (Food Chemistry, 2025)

AdaptiveGS: an explainable genomic selection framework based on adaptive stacking ensemble machine learning - Zhen Yang; Mei Song; Xianggeng Huang; Quanrui Rao; Shanghui Zhang; Zhongzheng Zhang; Chenyang Wang; Wenjia Li; Ran Qin; Chunhua Zhao; Yongzhen Wu; Han Sun; et al. (Theoretical and Applied Genetics, 2025)

Targeted discovery of oxygen-bridged sesquiterpenes from Cinnamomum migao by MS/MS-based molecular networking and their neuroprotective activities - Lang Zhou; Xiong Pan; Fa-ju Chen; Mei Peng; Yu Wang; Ming Gao; Li-shou Yang; Liang-qun Li; Juan Yang; Xiao-sheng Yang; Qi-ji Li (Phytochemistry, 2025)

Bipolar membrane electrodialysis for producing acid and alkali from concentrated seawater: Industrial application in Bohai Sea, China - Jia-Wang Qin; Shun Tang; Jia-Lin Shi; Teng-Fei Zhang; Lu Yang; Fang Wang; Liang Yin; Yuan-Fa Zhuang (Journal of Water Process Engineering, 2025)

Fabrication and application of ferrocene contained MOF derived porous carbon: A single multi-interference clean-up QuEChERS sorbent for facile analysis of triazine herbicides in various fruits and vegetables by LC-MS/MS - Zi-Ling Li; Da-Jin Yang; Jia-Qi Zhao; Wen-Jie Sun; Jie Gao; Shu-Feng Song; Hou-Jun Xu; Hai-Jie Li; Fa-Ming Tian; Man-Man Wang (Food Chemistry, 2025)

Glucose protects the pacific white shrimp Litopenaeus vannamei against Vibrio alginolyticus by inhibiting biofilm formation - Weibo Shi; Fa Dai; Ya Li; Zihao Sun; Min Meng; Qiuyan Yang; Weiwei Zhang (Fish & Shellfish Immunology, 2025)

Assessing the long-term impact of vegetation cover on sediment load within buffer zones of the upper Qin River Basin, Guangxi, China - Bin-rui Gan; Sheng-fa Yang; Wen Zhang (Environmental Fluid Mechanics, 2025)

Numerical investigation of aerated water entry by multiphase Riemann SPH method - Ke Zhao; Sheng-Fa Yang; Pei-Yin Yuan; Fu-Long Shi; Fu-Ren Ming (Ocean Engineering, 2025)

Evaluation of the efficacy and safety of omega-3 fatty acid nutritional supplements from Schizochytrium sp. in dog food - Zi-Xu Zhang; Yan-Cheng Lin; Min Lian; Ying-Feng Li; Jin-Fa Chen; Xue-Lian Ma; Dong-Sheng Guo; Guang Yang; Xiao-Man Sun (Algal Research, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

The deficiency of virulence factor AerA in Aeromonas veronii alleviates intestinal injury and microbiota disorders in largemouth bass (Micropterus salmoides) - Lu-Chuan Zhao; Ze-Sheng Zhang; Zhen-Zhen Yuan; Hui-Min Zhang; Jing-Bao Yang; Qian-Rong Liang; Shun-Fa Yi; Meng-Meng Huang; Hui Fei; Shun Yang (Fish & Shellfish Immunology, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

Helicobacter pylori VacA-induced gastric mucosal atrophy: a comparative analysis with other forms of atrophic gastritis - Yang-Kun Wang; Wen-Rui Chen; Ling-Yan Lu; Ying-Ying Li; Rui-Kun Qiu; Chao-Ya Zhu; Fa-Shun Zhang; Su-Nan Wang; Si-Liang Xu (Journal of Molecular Histology, 2025)

Habrobracon hebetor ectoparasitism paralyzing effect on Corcyra cephalonica of different instar larvae - Yi Mao; Hou-ding Ou; Xin Jin; Xiu-qin Wang; Yao Huang; Mao-fa Yang (Journal of Stored Products Research, 2025)

Chlorpyrifos-oxon results in autophagic flux dysfunction contributing to neuronal apoptosis via a ROS/AMPK/CHOP activation pathway - Jui-Ming Liu; Kuan-I Lee; Chin-Chuan Su; Kai-Min Fang; Shing-Hwa Liu; Shih-Chang Fu; Chun-Ying Kuo; Kai-Chih Chang; Jun-An Ke; Ya-Wen Chen; Ching-Yao Yang; Chun-Fa Huang (Chemico-Biological Interactions, 2025)

CTHRC1 expresses in cancer-associated fibroblasts and is associated with resistance to anti-androgen therapy in prostate cancer - Hai-qi Liang; Qi-huan He; Qiu-ju Wei; Qi-zhou Mo; Guang-lin Yang; Fa-ye Wei; Li-wei Wei; Yu-jian Li; Min Qin; Ji-wen Cheng (Genes & Genomics, 2025)

Dietary pyridoxine promoted muscle protein deposition relating to PI3K/AKT/TOR pathway and the ubiquitin proteasome system in grass carp (Ctenopharyngodon idella) - Li-Fu Gong; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Fa-Li Wu; Yang Liu (Food Bioscience, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

Rainfall Promote Bruceine D Release from Brucea javanica Leaf Litter Thus Reducing Weeds and Enhancing Plant Competitiveness - Yao Tong; Hai-Ou Lin; Dong-Qiang Zeng; Fa-Yang Xie; Wen-Wei Tang (Journal of Chemical Ecology, 2025)

The herbicide 2,4-dichlorophenoxyacetic acid induces pancreatic β-cell death via oxidative stress-activated AMPKα signal downstream-regulated apoptotic pathway - Ken-An Lin; Chin-Chuan Su; Kuan-I Lee; Shing-Hwa Liu; Kai-Min Fang; Chih-Hsin Tang; Wei-Cheng Lia; Chun-Ying Kuo; Kai-Chih Chang; Chun-Fa Huang; Ya-Wen Chen; Ching-Yao Yang (Toxicology Letters, 2025)

Exploring eutrophic effects of marine sediments underneath fish cage farms: Insights from changes in eukaryotic and bacterial communities and volatile organic compounds - Fa-Guo Wan; Yong-Long Chen; Jia-Lang Zheng; Wang-Yang Jin; Tian-Hong Chen; Qing-Ling Zhu; Qing-Hao Zhan; Li-Hua Jiang; Shun Chen; Wei-Hua Song; Xiao-Jun Yan (Science of The Total Environment, 2025)

Low-Frequency Sweep Design—A Case Study in Middle East Desert Environments - Yong-fei Qi; Zhou-hong Wei; Ming-tao Nie; Guo-fa Li; Tao Wang; Hai Ling; Sheng-kui Cong; Xin-yang Chen; Chang-ping Duan; Yang Liu (Applied Geophysics, 2025)

Equilibrium boron isotope fractionation during kaolinite adsorption and applications to chemical weathering processes - Yin-Chuan Li; Ya-Ru Zhou; Hai-Zhen Wei; Martin R. Palmer; Fa-Yang Guo; Yong-Hui Li; Yong-An Qi; Da-Ping Xia (Geochimica et Cosmochimica Acta, 2025)

Development of a novel ternary MOF nanozyme-based smartphone-integrated colorimetric and microfluidic paper-based analytical device for trace glyphosate detection - Ting Zhang; Miao Tang; SiYi Yang; Huanbao Fa; Yongzhong Wang; Danqun Huo; Changjun Hou; Mei Yang (Food Chemistry, 2025)

Smartphone-based dual-mode aptasensor with bifunctional metal-organic frameworks as signal probes for ochratoxin A detection - Yu-Long Li; Yan-Yue Chen; Fa-Ting Xie; Qiu-Xia Li; Tong Yang; Yun-Hui Yang; Rong Hu (Food Chemistry, 2025)

The Role of SIRT1–BDNF Signaling Pathway in Fluoride-Induced Toxicity for Glial BV-2 Cells - Bo Yang; Feiqing Wang; Xu Yang; Xiaoshuang Yuan; Yuting Yang; Xiaoxu Chen; Tingting Tian; Fa Chen; Dongxin Tang; Zhixu He; Yang Liu; Yanju Li (Biological Trace Element Research, 2025)

Comparative analysis of carotenoids, fatty acids, minerals, tastes, and odor in the skin of wild versus farmed large yellow croaker: Superior nutritional benefits with elevated heavy metal risks - Jia-Lang Zheng; Tao Zhu; Wang-Yang Jin; Qing-Hao Zhan; Fa-Guo Wan; Yong-Long Chen; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Shuang Chen; Wei-Ye Li; Yi-Fan Liu; et al. (Aquaculture, 2025)

Corrigendum to “Bacillus licheniformis ameliorates Aflatoxin B1-induced testicular damage by improving the gut-metabolism-testis axis” [J Hazard Mater 468 (2024) 133836] - Fa-Li Zhang; Hao-Hai Ma; Pei-Yu Dong; Yu-Mei Chen Yan; Yu Chen; Guo-Ming Yang; Wei Shen; Xi-Feng Zhang (Journal of Hazardous Materials, 2025)

Effect of Maillard reaction on the allergenicity of crude extract of Mactra quadrangularis - Fa-Jie Li; Xin-Rong He; Dong-Xiao Li; Yang Yang; Shuai Kang; Qing-Mei Liu; Lian-Zhong Luo; Gui-Xia Chen; Guang-Ming Liu (Food Research International, 2025)

The change rule of lipid oxidation and hydrolysis driven via water in Antarctic krill oil: Based on association colloid formation - Xue-Chen Pei; Xiang-Bo Zeng; De-Yang Li; Xin-Miao Wang; Fa-Wen Yin; Hui-Lin Liu; Da-Yong Zhou (Food Chemistry, 2025)

Density-dependent fitness and mass-rearing of Habrobracon hebetor (Say) (Hymenoptera: Braconidae) incorporating life table variability - Hou-Ding Ou; Xiu-Qin Wang; Yao Huang; Lan Wei; Xiao-Fei Yu; Mao-Fa Yang (Journal of Stored Products Research, 2024)

In-situ and ex-situ selective catalysis of biochar-based catalysts for the production of high-quality bio-oil and H2-rich gas from tobacco stem - Xin Tang; Xiang Yang Li; Qiu Fa He; Yao Peng; Bin Peng; Yu Zhang; Wei Luo; Zhi Zhou (Journal of Environmental Chemical Engineering, 2024)

Bioassay-guided separation of antioxidants in Blaps rynchopetera Fairmaire and their theoretical mechanism - Zhenni Ji; Chang Liu; Fa Xu; Yi Wang; Dongyu Gu; Yun Huang; Yi Yang (Journal of Asia-Pacific Entomology, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Risk of New-onset Stroke in Patients with Type 2 Diabetes with Chronic Kidney Disease on Sodium-glucose Co-transporter-2 Inhibitor Users - Gwo-Ping Jong; Tsung-Kun Lin; Pei-Lun Liao; Jing-Yang Huang; Tsung-Yuan Yang; Lung-Fa Pan (Translational Stroke Research, 2024)
Clinical studies have investigated the effects of using sodium-glucose co-transporter-2 (SGLT2) inhibitors on the development of new-onset stroke (NOS) in patients with type 2 diabetes (T2D) and chronic kidney disease (CKD), but the findings are inconsistent. This study aimed to examine the association between the use of SGLT2 inhibitors and NOS risk in patients with T2D and CKD. We conducted a nationwide retrospective cohort study using data from the Taiwan Health Insurance Review and Assessment Service database for the years 2004 to 2019. The primary outcome was the risk of incident stroke, which was estimated using hazard ratios (HRs) and 95% confidence intervals (CIs). We used multiple Cox regression modeling to analyze the association between SGLT2 inhibitor use and the risk of stroke in patients with T2D and CKD. In a cohort of 113,710 patients with T2D and CKD who were using SGLT2 inhibitors and 227,420 patients with T2D and CKD who were not using SGLT2 inhibitors, after applying a 1:2 sex- and age-matching strategy, 2,842 and 7,169 NOS events were recorded, respectively. The event rate per 10,000 person-months was 10.60 (95% CI 10.21 to 11.03) for SGLT2 inhibitor users and 13.71 (13.39–14.03) for non-SGLT2 inhibitor users. After adjusting for the index year, sex, age, comorbidities, and concurrent medication, there was a decreased risk of NOS for SGLT2 inhibitor users (adjusted HR 0.80; 95% CI 0.77–0.84) compared with non-SGLT2 inhibitor users. The sensitivity test for the propensity score 1:1-matched analyses showed similar results (adjusted HR 0.80; 95% CI 0.76–0.84). The type of SGLT2 inhibitor subgroup analysis for incident stroke showed consistent results. We concluded that the use of SGLT2 inhibitors in patients with T2D and CKD was associated with significantly low rates of NOS. The significantly low rates of NOS in patients with T2D and CKD were greater among females and less than 50 years patients.

Design and Development of 10,000-Meter Class Autonomous Underwater Vehicle - Jiali Xu; Zhaopeng Du; Xianqing Huang; Chong Ren; Shuai Fa; Shaoqiong Yang (Journal of Marine Science and Engineering, 2024)
As a significant subset of unmanned underwater vehicles (UUVs), autonomous underwater vehicles (AUVs) possess the capability to autonomously execute tasks. Characterized by its flexibility, cost-effectiveness, extensive operational range, and robust environmental adaptability, AUV has emerged as the primary technological apparatus for deep-sea exploration and research. In this paper, we present the design of a 10,000 m class AUV equipped with capabilities such as fixed-depth navigation, regional autonomous cruising, full-depth video recording, and temperature and salinity profiling. Initially, we outline the comprehensive design of the AUV, detailing its structural configuration, system components, functional module arrangement, and operational principles. Subsequently, we compute the hydrodynamic parameters using a spatial kinematics model. Finally, the AUV designed in this paper is tested for its functions and performance, such as fixed-depth sailing, maximum speed, and maximum diving depth, and its reliability and practicability are verified.

Mechanism of discoloration of Antarctic krill oil upon storage: A study based on model systems - Xiang-Bo Zeng; Xue-Chen Pei; De-Yang Li; Fa-Wen Yin; Hui-Lin Liu; Meng-Ling Jin; Jiang-Hua Zhang; Da-Yong Zhou (Food Chemistry, 2024)

Calreticulin from Apostichopus japonicus relieves endoplasmic reticulum stress induced by Vibrio splendidus through autophagy - Weikang Liang; Lincheng Hu; Fa Dai; Yue Shi; Lei Yang; Chenghua Li (Fish & Shellfish Immunology, 2024)

MBene as novel and effective electrochemical material used to enhance paper-based biosensor for point-of-care testing ctDNA from mice serum - Siyi Yang; Liangyi Zhao; Xiao Yang; Liyu Yang; Huanbao Fa; Yongzhong Wang; Danqun Huo; Changjun Hou; Daidi Zhong; Mei Yang (Chemical Engineering Journal, 2024)

Lowering Schottky barrier in MoC-based cocatalyst via heteroatoms tunning for enhanced photocatalytic hydrogen evolution - Ru-zhou Miao; Yu-long Bao; Guang Yang; Ying-jie Sun; Xiao-jing Wang; Jun Zhao; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2024)

Sodium Fluoride Exposure Induces Developmental Toxicity and Cardiotoxicity in Zebrafish Embryos - Feiqing Wang; Fa Chen; Wen Song; Yanju Li; Haiyan Wu; Tingting Tian; Mengxian Tian; Dongxin Tang; Yang Liu (Biological Trace Element Research, 2024)

Positive temperature coefficient material based on silicone rubber/ paraffin/ graphite/ carbon nanotubes for wearable thermal management devices - Jian-Min Hao; Yin-Fa Yang; Yi-Tao Shen; Rui Zhou; Wei Zhang; Hua Chen; Wen-Long Cheng (Chemical Engineering Journal, 2024)

Niche convergence and biogeographic history shape elevational tree community assembly in a subtropical mountain forest - Liang-Liang Ma; Sebastian Seibold; Marc W. Cadotte; Jia-Yun Zou; Jie Song; Zhi-Qiong Mo; Shao-Lin Tan; Lin-Jiang Ye; Wei Zheng; Kevin S. Burgess; Zhi-Fa Chen; De-Tuan Liu; et al. (Science of The Total Environment, 2024)

Mechanism of color change in Antarctic krill oil during storage - Xiang-Bo Zeng; Fa-Wen Yin; Guan-Hua Zhao; Chao Guo; De-Yang Li; Hui-Lin Liu; Lei Qin; Fereidoon Shahidi; Da-Yong Zhou (Food Chemistry, 2024)

Influences of removable gas injection methods on the temperature field and gas composition of the underground coal gasification process - Fa-qiang Su; Jun-nan Yang; Xiao-long He; Meng-jia Dai; Akihiro Hamanaka; Yi- he Yu; Wen Li; Jiao-yuan Li (Fuel, 2024)

Bacillus licheniformis ameliorates Aflatoxin B1-induced testicular damage by improving the gut-metabolism-testis axis - Fa-Li Zhang; Hao-Hai Ma; Pei-Yu Dong; Yu-Mei Chen Yan; Yu Chen; Guo-Ming Yang; Wei Shen; Xi-Feng Zhang (Journal of Hazardous Materials, 2024)

Windows of sensitivity for risk of adverse birth outcomes related to gestational PM2.5 exposure: Evidence from a natural experiment - Wei Ni; Yuhan Xing; Guoju Li; Zhanhui Du; Ping Yang; Qinzheng Wang; Xinmeng Yang; Bei Lyu; Hongge Fa; Qiuling Shi; Quansheng Xing (Environmental Pollution, 2024)

Quantitative trait loci detection for three tiller-related traits and the effects on wheat (Triticum aestivum L.) yields - Yibiao Cai; Xiaohan Zhou; Chenyang Wang; Aifeng Liu; Zhencang Sun; Shihui Li; Xinyao Shi; Shuang Yang; Yuxiang Guan; Jiajia Cheng; Yongzhen Wu; Ran Qin; et al. (Theoretical and Applied Genetics, 2024)

Numerical simulation analysis of debris filtration in the bottom nozzle - Shuang Deng; Quan-yao Ren; Jing Zhang; Xin Duan; Fa-wen Zhu; Yong Xin; Xin-Yu Yang; Quan Li; Ying-wei Wu (Annals of Nuclear Energy, 2024)

Examination of the effects of triacylglycerol lipase on astaxanthin conversion in the black tiger prawn Penaeus monodon - Xin-Tao Li; Li-Shi Yang; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Fa-Lin Zhou; Yun-Dong Li; Jian-Zhi Shi; Xu Chen; Yu-kai Yang; Jian-Hua Huang (Aquaculture, 2024)

A new dead reckoning method for HAUVs assisted by a dynamic model with ocean current information - Shaoqiong Yang; Xiaowen Shang; Tongshuai Sun; Xuehao Wang; Haitong Zhao; Shuai Fa; Yanhui Wang (Ocean Engineering, 2024)

Fine mapping of a major QTL, qKl-1BL controlling kernel length in common wheat - Ran Qin; Mingsu Cao; Jizi Dong; Linqu Chen; Haoru Guo; Qingjie Guo; Yibiao Cai; Lei Han; Zhenjie Huang; Ninghao Xu; Aoyu Yang; Huiyuan Xu; et al. (Theoretical and Applied Genetics, 2024)

Optimization of ultrasound-assisted extraction of glycyrrhizic acid and glabridin from Glycyrrhiza glabra L. using response surface methodology and development of a green analytical method - Ye-fei Liang; Qing Wen; Zhen-fei Yang; Cui-qin Li; Fa-rong Li (Sustainable Chemistry and Pharmacy, 2024)

Confined bismuth single atoms and nanoparticles dual-sites constructed via reverse etching for CO2 photoreduction to CH4 - Dou Zhang; Ying-jie Sun; Kai-hua Zhang; Guang Yang; Xiao-jing Wang; Yi-lei Li; Hui-yun Han; Xinying Liu; Bao-Hang Han; Fa-tang Li (Chemical Engineering Journal, 2024)

Effective degradation of zearalenone by dye-decolorizing peroxidases from Pleurotus ostreatus and its metabolic pathway and toxicity analysis - Shuai Ding; Chen Lin; Qiuyun Xiao; Fa Feng; Junfeng Wang; Xing Zhang; Shengjing Yang; Lingling Li; Fei Li (Science of The Total Environment, 2024)

Enhancing flame retardancy, mechanical durability, and anti-aging property of polyurethane foam via novel cyclic phosphonate - Zhi-Cheng Fu; Fa-Yang Bu; Zhe-Peng Li; Ting Wang; Jin-Ni Deng; Hai-Bo Zhao; Sheng-Chao Huang; Yu-Zhong Wang; Ming-Jun Chen (Chemical Engineering Journal, 2024)

Chiral Au nanostars for SERS sensing of enantiomers discrimination, multibacteria recognition and photothermal antibacterial application - Xueqin Huang; Qiuxia Chen; Yiling Ma; Chan Huang; Weixia Zhi; Jiahao Li; Runmin Zeng; Jiang Pi; Jun-fa Xu; Jun Xu; Wanyong Yang; Jianglin Zhang; et al. (Chemical Engineering Journal, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Sublethal and transgenerational effects of broflanilide on Myzus persicae (Sulzer) (Hemiptera: Aphididae) - Sen-Wen Zhang; Qing-Hui Zeng; Hong Yang; Chao Zhang; Bo Ding; Han-Zhi Yang; Mao-Fa Yang (Crop Protection, 2023)

Underwater glider trajectory control based on virtual hinges of multi-body model - Shuai Li; Yanhui Wang; Muhua Ren; Wendong Niu; Ming Yang; Shaoqiong Yang; Xuehao Wang; Shuai Fa (Ocean Engineering, 2023)

Engineering properties and optimal design of foam lightweight soil composite fly ash: An eco-friendly subgrade material - Chen Zhang; Zhiduo Zhu; Yue Zhang; Fa Liu; Yang Yang; Yu Wan; Wangwen Huo; Liu Yang (Journal of Cleaner Production, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Four previously undescribed diketopiperazines from marine fungus Aspergillus puniceus FAHY0085 and their effects on liver X receptor α - Qi Hong; Miao-Miao Guo; Jin Yang; Xing Wei; Li Liao; Xiu-Juan Xin; Di Zhang; Fa-Liang An (Phytochemistry, 2023)

Testing, simulation, and design for analyzing the behavior of lined pipes under torsion - Zhen-xing Zhu; Lu Yang; Fa-cheng Wang; Yi Gang (Ocean Engineering, 2023)

Design and analysis of wire-driven tail fin for bionic underwater glider - Liming Ge; Wenda Ma; Shaoqiong Yang; Xiao Yu; Tongshuai Sun; Xuan Wang; Shuai Fa; Yanhui Wang (Ocean Engineering, 2023)

Characterization and fine mapping analysis of a major stable QTL qKnps-4A for kernel number per spike in wheat - Ran Qin; Tianhang Ma; Yibiao Cai; Xinyao Shi; Jiajia Cheng; Jizi Dong; Chenyang Wang; Shihui Li; Guoqing Pan; Yuxiang Guan; Lei Zhang; Shuang Yang; et al. (Theoretical and Applied Genetics, 2023)

High-efficient electromagnetic wave absorption of coral-like Co/CoO/RGO hybrid aerogels with good hydrophobic and thermal insulation properties - Yuan Shu; Tingkai Zhao; Jalil abdul; Xianghong Li; Lei Yang; Fa Luo (Chemical Engineering Journal, 2023)

In vivo antibacterial activity of medicinal plant Sophora flavescens against Streptococcus agalactiae infection - Fa‐Li Zhang; Liu Yang; Wei‐Hao He; Ling‐Jun Xie; Fei Yang; Ying‐Hui Wang; Ai‐Guo Huang (Journal of Fish Diseases, 2023)
Streptococcosis disease caused by Streptococcus agalactiae (Group B Streptococcus, GBS) results in a huge economic loss of tilapia culture. It is urgent to find new antimicrobial agents against streptococcosis. In this study, 20 medicinal plants were evaluated in vitro and in vivo to obtain medicinal plants and potential bioactive compounds against GBS infection. The results showed that the ethanol extracts of 20 medicinal plants had low or no antibacterial properties in vitro, with a minimal inhibitory concentration ≥256 mg/L. Interestingly, in vivo tests showed that 7 medicinal plants could significantly inhibit GBS infection in tilapia, and Sophora flavescens (SF) had the strongest anti‐GBS activity in tilapia, reaching 92.68%. SF could significantly reduce the bacterial loads of GBS in different tissues (liver, spleen and brain) of tilapia after treated with different tested concentrations (12.5, 25.0, 50.0 and 100.0 mg/kg) for 24 h. Moreover, 50 mg/kg SF could significantly improve the survival rate of GBS‐infected tilapia by inhibiting GBS replication. Furthermore, the expression of antioxidant gene cat , immune‐related gene c‐type lysozyme and anti‐inflammatory cytokine il‐10 in liver tissue of GBS‐infected tilapia significantly increased after treated with SF for 24 h. Meanwhile, SF significantly reduced the expression of immune‐related gene myd88 and pro‐inflammatory cytokines il‐8 and il‐1β in liver tissue of GBS‐infected tilapia. The negative and positive models of UPLC‐QE‐MS, respectively, identified 27 and 57 components of SF. The major components of SF extract in the negative model were α, α‐trehalose, DL‐malic acid, D‐ (−)‐fructose and xanthohumol, while in the positive model were oxymatrine, formononetin, (−)‐maackiain and xanthohumol. Interestingly, oxymatrine and xanthohumol could significantly inhibit GBS infection in tilapia. Taken together, these results suggest that SF can inhibit GBS infection in tilapia, and it has potential for the development of anti‐GBS agents.

Cinnamigones A–C, three highly oxidized guaiane-type sesquiterpenes with neuroprotective activity from Cinnamomum migao - Lang Zhou; Li-shou Yang; Li Wang; Hua-dan Liu; Ming Gao; Fa-ju Chen; Juan Yang; Qi-ji Li; Xiao-sheng Yang (Phytochemistry, 2023)

First transcriptome profiling in gill and hepatopancrease tissues of Metapenaeus ensis in response to acute ammonia-N stress - Yun-Dong Li; Meng-Ru Si; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Li-Shi Yang; Jian-Hua Huang; Fa-Lin Zhou (Fish & Shellfish Immunology, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Effect of Tyrosol Acyl Esters on the Antioxidant Status of Mussel ( Mytilus edulis ) Oil During Accelerated Oxidative Storage - Qian Wang; Mo-Tong Zhang; Xin-Miao Wang; Guan-Hua Zhao; Yuan-Yuan Hu; Fa-Wen Yin; Hui-Lin Liu; Xiao-Yang Liu; Da-Yong Zhou (Journal of Aquatic Food Product Technology, 2023)

Adverse impacts of development on the deltamethrin-exposed host Ephestia elutella (Lepidoptera: Pyralidae) on population parameters of Habrobracon hebetor (Hymenoptera: Braconidae) - Xiu-Qin Wang; Hou-Ding Ou; Hao-Xi Li; Lan Wei; Yao Huang; Mao-Fa Yang (Crop Protection, 2023)

Vapor-deposited digenite in Chang’e-5 lunar soil - Zhuang Guo; Chen Li; Yang Li; Yanxue Wu; Chenxi Zhu; Yuanyun Wen; Wenzhe Fa; Xiongyao Li; Jianzhong Liu; Ziyuan Ouyang (Science Bulletin, 2023)

In-situ growth of carbon nanotubes for improving the performance of Co-N/C catalysts in proton exchange membrane fuel cell - Xi-Ming Qu; Shu-Hu Yin; Ya-Ni Yan; Jian Yang; Yan-Rong Li; Xiao-Yang Cheng; Fa Lu; Chong-Tai Wang; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Effects of long-term grazing exclusion on vegetation structure, soil water holding capacity, carbon and nitrogen sequestration capacity in an alpine meadow on the Tibetan Plateau - Yong-sheng Yang; Fa-wei Zhang; Xian-rong Xie; Jun-bang Wang; Ying-nian Li; Xiao-tao Huang; Hui-ting Li; Hua-kun Zhou (Journal of Mountain Science, 2023)

Interface engineering of hybrid ZnCo2O4@Ni2.5Mo6S6.7 structures for flexible energy storage and alkaline water splitting - Wen-Duo Yang; Rong-Da Zhao; Fang-Yu Guo; Jun Xiang; Sroeurb Loy; Liang Liu; Jia-Yu Dai; Fu-Fa Wu (Chemical Engineering Journal, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Petrogenesis of Eocene mafic and felsic magmas in the New Caledonia ophiolite: geochemistry and geochronology constraints - Yang Xu; Chuan-Zhou Liu; Xue-Fa Shi; Wei Lin (International Geology Review, 2022)

High Levels of 25-OH-Vitamin D and Copper in Pregnant Women with Abnormal Glucose Challenge Test - Chien-Hua Chiang; Wan-Ju Kung; Chien-Hung Lee; Yeong-Hwa Zen; Cheng-Fa Lee; Hui-Ru Yang; Ching-Chiang Lin; Yeou-Lih Huang (Biological Trace Element Research, 2022)

Anterior Cingulate Cortex Mediates Hyperalgesia and Anxiety Induced by Chronic Pancreatitis in Rats - Dan Ren; Jia-Ni Li; Xin-Tong Qiu; Fa-Ping Wan; Zhen-Yu Wu; Bo-Yuan Fan; Ming-Ming Zhang; Tao Chen; Hui Li; Yang Bai; Yun-Qing Li (Neuroscience Bulletin, 2022)
Central sensitization is essential in maintaining chronic pain induced by chronic pancreatitis (CP), but cortical modulation of painful CP remains elusive. Here, we examined the role of the anterior cingulate cortex (ACC) in the pathogenesis of abdominal hyperalgesia in a rat model of CP induced by intraductal administration of trinitrobenzene sulfonic acid (TNBS). TNBS treatment resulted in long-term abdominal hyperalgesia and anxiety in rats. Morphological data indicated that painful CP induced a significant increase in FOS-expressing neurons in the nucleus tractus solitarii (NTS) and ACC, and some FOS-expressing neurons in the NTS projected to the ACC. In addition, a larger portion of ascending fibers from the NTS innervated pyramidal neurons, the neural subpopulation primarily expressing FOS under the condition of painful CP, rather than GABAergic neurons within the ACC. CP rats showed increased expression of vesicular glutamate transporter 1, and increased membrane trafficking and phosphorylation of the N -methyl-D-aspartate receptor (NMDAR) subunit NR2B and the α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptor (AMPAR) subunit GluR1 within the ACC. Microinjection of NMDAR and AMPAR antagonists into the ACC to block excitatory synaptic transmission significantly attenuated abdominal hyperalgesia in CP rats, which was similar to the analgesic effect of endomorphins injected into the ACC. Specifically inhibiting the excitability of ACC pyramidal cells via chemogenetics reduced both hyperalgesia and comorbid anxiety, whereas activating these neurons via optogenetics failed to aggravate hyperalgesia and anxiety in CP rats. Taken together, these findings provide neurocircuit, biochemical, and behavioral evidence for involvement of the ACC in hyperalgesia and anxiety in CP rats, as well as novel insights into the cortical modulation of painful CP, and highlights the ACC as a potential target for neuromodulatory interventions in the treatment of painful CP.

Doubled production of cordycepin analogs in cultured Cordyceps militaris by addition of Andrea droppings - Tzu-Yun Chou; Hsiao-Ping Kuo; Sheng-Fa Tsai; Shyue-Tsong Huang; Meei-Ju Yang; Shoei-Sheng Lee; Chia-Chuan Chang (Natural Product Research, 2021)

Nitrogen contaminants damage on intestinal epithelial tight junctions: a review - Guo-ping Zhao; Jin-wang Li; Fang-wei Yang; Xiao-yu Wang; Fa-zheng Ren; Guo-fang Pang; Yi-xuan Li (Environmental Chemistry Letters, 2021)

Genome editing of Corynebacterium glutamicum mediated with Cpf1 plus Ku/LigD - Fa-Yu Yang; Nan Wei; Zhi-Hao Zhang; Mi Wang; Ying-Chun Liu; Li-Fang Zhang; Feng Gu (Biotechnology Letters, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Comparison of the Bulk and Rhizosphere Soil Prokaryotic Communities Between Wild and Reintroduced Manglietiastrum sinicum Plants, a Threatened Species with Extremely Small Populations - Dai-Fa Su; Qing-Qing Shen; Jun-Yu Yang; Zhi-Ying Li; Wei Xiao; Yong-Xia Wang; Zhang-Gui Ding; Xiao-Long Cui (Current Microbiology, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Crenobacter intestini sp. nov., Isolated from the Intestinal Tract of Konosirus punctatus - Song-Biao Shi; Jia-Fa Wu; Li-Fang Yang; Ming-Guo Jiang; Cai-Mi Gao; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Compound heterozygous mutation of the ASXL3 gene causes autosomal recessive congenital heart disease - Fang Fu; Ru Li; Ting-ying Lei; Dan Wang; Xin Yang; Jin Han; Min Pan; Li Zhen; Jian Li; Fa-tao Li; Xiang-yi Jing; Dong-zhi Li; et al. (Human Genetics, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Short-term streamflow time series prediction model by machine learning tool based on data preprocessing technique and swarm intelligence algorithm - Wen-Jing Niu; Zhong-Kai Feng; Wen-Fa Yang; Jun Zhang (Hydrological Sciences Journal, 2020)

Surface fractal dimensions as a characterization parameter for methane adsorption–induced coal strains - Jie Zhu; Yang Zhang; Rui Zhang; Bo Zhang; Jun Tang; Fa He (Arabian Journal of Geosciences, 2020)

Nonstationary signal inversion based on shaping regularization for random noise attenuation - Wu-Yang Yang; Wei Wang; Guo-Fa Li; Xin-Jian Wei; Wan-Li Wang; De-wu Chen (Applied Geophysics, 2020)

Synthesis and antitumor activity of camptothecin- 4β-triazolopodophyllotoxin conjugates - Cheng-Ting Zi; Liu Yang; Fa-Wu Dong; Qing-Hua Kong; Zhong-Tao Ding; Jun Zhou; Zi-Hua Jiang; Jiang-Miao Hu (Natural Product Research, 2020)

Automatic Identification of Clear-Air Echoes Based on Millimeter-wave Cloud Radar Measurements - Ling Yang; Yun Wang; Zhongke Wang; Qian Yang; Xingang Fan; Fa Tao; Xiaoqiong Zhen; Zhipeng Yang (Advances in Atmospheric Sciences, 2020)

Tenuazonic acid-induced change in volatile emission from rose plants and its chemometrical analysis - Fa-zhong Yang; Yun-xian Li; Min Tang; Guo-lei Zhu; Shi-ping Zhou; Bin Yang (Journal of Plant Diseases and Protection, 2020)

New insights into antimetastatic signaling pathways of melatonin in skeletomuscular sarcoma of childhood and adolescence - Ko-Hsiu Lu; Chiao-Wen Lin; Yi-Hsien Hsieh; Shih-Chi Su; Russel J. Reiter; Shun-Fa Yang (Cancer and Metastasis Reviews, 2020)

Effects of Exogenous GA3 and DPC Treatments on Levels of Endogenous Hormone and Expression of Key Gibberellin Biosynthesis Pathway Genes During Stem Elongation in Sugarcane - Li-Hang Qiu; Rong-Fa Chen; Han-Min Luo; Ye-Geng Fan; Xing Huang; Jun-Xian Liu; Fa-Qian Xiong; Hui-Wen Zhou; Chong-Kun Gan; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2019)

Mutational signatures and mutagenic impacts associated with betel quid chewing in oral squamous cell carcinoma - Shih-Chi Su; Lun-Ching Chang; Chiao-Wen Lin; Mu-Kuan Chen; Chun-Ping Yu; Wen-Hung Chung; Shun-Fa Yang (Human Genetics, 2019)

Toxicity, residue, degradation and detection methods of the insecticide triazophos - Fang-Wei Yang; Yi-Xuan Li; Fa-Zheng Ren; Ran Wang; Guo-Fang Pang (Environmental Chemistry Letters, 2019)

Pathological and therapeutic aspects of matrix metalloproteinases: implications in childhood leukemia - Yi-Hsuan Hsiao; Shih-Chi Su; Chiao-Wen Lin; Yu-Hua Chao; Wei-En Yang; Shun-Fa Yang (Cancer and Metastasis Reviews, 2019)

Association of the Polygenic Risk Score with the Incidence Risk of Parkinson’s Disease and Cerebrospinal Fluid α-Synuclein in a Chinese Cohort - Wei-Wei Li; Dong-Yu Fan; Ying-Ying Shen; Fa-Ying Zhou; Yang Chen; Ye-Ran Wang; Heng Yang; Jing Mei; Ling Li; Zhi-Qiang Xu; Yan-Jiang Wang (Neurotoxicity Research, 2019)

Genetic Association Between NGFR, ADAM17 Gene Polymorphism, and Parkinson’s Disease in the Chinese Han Population - Wei-Wei Li; Ying-Ying Shen; Dong-Wan Chen; Hui-Yun Li; Qian-Qian Shi; Jing Mei; Heng Yang; Fa-Ying Zhou; An-Yu Shi; Tao Zhang; Xiu-Qing Yao; Zhi-Qiang Xu; et al. (Neurotoxicity Research, 2019)

Assessing the influence of the minimum measured diameter on forest spatial patterns and nearest neighborhood relationships - Yuan-fa Li; Hai-peng Yang; Hong-xiang Wang; Shao-ming Ye; Wen-zhen Liu (Journal of Mountain Science, 2019)

Ottowia flava sp. nov., isolated from fish intestines - Song-Biao Shi; Gui-Ding Li; Li-Fang Yang; Cong Liu; Ming-Guo Jiang; Qin-Yuan Li; Jia-Fa Wu; Kun Zhang; Long-Qian Jiang; Nai-Kun Shen; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Disruption of stcA blocks sterigmatocystin biosynthesis and improves echinocandin B production in Aspergillus delacroxii - Taoling Min; Lei Xiong; Yan Liang; Rui Xu; Chenchang Fa; Sheng Yang; Haifeng Hu (World Journal of Microbiology and Biotechnology, 2019)

Reference evapotranspiration concentration and its relationship with precipitation concentration at southern and northern slopes of Tianshan Mountains, China - Fa-rong Huang; Tao Yang; Qian Li; Si-si Li; Lan-hai Li; Suwannee Adsavakulchai (Journal of Mountain Science, 2019)

The niches of nuthatches affect their lineage evolution differently across latitude - Yu‐Chi Chen; Masoud Nazarizadeh; Fu‐Min Lei; Xiao‐Jun Yang; Cheng‐Te Yao; Feng Dong; Lu Dong; Fa‐Sheng Zou; Sergei V. Drovetski; Yang Liu; Chun‐Cheng Huang; Chih‐Ming Hung (Molecular Ecology, 2019)
Ecological niche evolution can promote or hinder the differentiation of taxa and determine their distribution. Niche‐mediated evolution may differ among climatic regimes, and thus, species that occur across a wide latitudinal range offer a chance to test these heterogeneous evolutionary processes. In this study, we examine (a) how many lineages have evolved across the continent‐wide range of the Eurasian nuthatch ( Sitta europaea ), (b) whether the lineages’ niches are significantly divergent or conserved and (c) how their niche evolution explains their geographic distribution. Phylogenetic reconstruction and ecological niche models (ENMs) showed that the Eurasian nuthatch contained six parapatric lineages that diverged within 2 Myr and did not share identical climatic niches. However, the niche discrepancy between these distinct lineages was relatively conserved compared with the environmental differences between their ranges and thus was unlikely to drive lineage divergence. The ENMs of southern lineages tended to cross‐predict with their neighbouring lineages whereas those of northern lineages generally matched with their abutting ranges. The coalescence‐based analyses revealed more stable populations for the southern lineages than the northern ones during the last glaciation cycle. In contrast to the overlapping ENMs, the smaller parapatric distribution suggests that the southern lineages might have experienced competitive exclusion to prevent them from becoming sympatric. On the other hand, the northern lineages have expanded their ranges and their current abutting distribution might have resulted from lineages adapting to different climatic conditions in allopatry. This study suggests that niche evolution may affect lineage distribution in different ways across latitude.

Avalanche activity and characteristics of its triggering factors in the western Tianshan Mountains, China - Jian-sheng Hao; Fa-rong Huang; Yang Liu; Chukwudi Amanambu Amobichukwu; Lan-hai Li (Journal of Mountain Science, 2018)

Different behavioral, neural and neuropeptide responses of fathers to their own and to alien pups in mandarin voles - Wei Yuan; Xiang-Ping Yang; Peng Yu; Rui Jia; Fa-Dao Tai; Bin Wei; Xiao Liu; Lei-Ge Ma (Journal of Comparative Physiology A, 2018)

Post-Yield Properties of Rock Salt Using the Concept of Mobilized Strength Components and the Dilation Angle - Linjian Ma; Fa Yang; Hongfa Xu; Zhinan Xie (Geotechnical and Geological Engineering, 2017)

ACOS5 is required for primexine formation and exine pattern formation during microsporogenesis in Arabidopsis - Hui-hui Xie; Lin Chen; Fa-qing Xu; Wan-sheng Guo; Shui Wang; Zhong-nan Yang; Sen Zhang (Journal of Plant Biology, 2017)

Characterization of the temporal and spatial expression of wheat (Triticum aestivum L.) plant height at the QTL level and their influence on yield-related traits - Na Zhang; Xiaoli Fan; Fa Cui; Chunhua Zhao; Wei Zhang; Xueqiang Zhao; Lijuan Yang; Ruiqing Pan; Mei Chen; Jie Han; Jun Ji; Dongcheng Liu; et al. (Theoretical and Applied Genetics, 2017)

Four new glycosides from the stems of Dendrobium fimbriatum Hook - Feng-Qing Xu; Wei-Wei Fan; Cheng-Ting Zi; Fa-Wu Dong; Dan Yang; Jun Zhou; Jiang-Miao Hu (Natural Product Research, 2017)

Morphology and controlling factors of the longitudinal profile of gullies in the Yuanmou dry-hot valley - Lin Ding; Fa-chao Qin; Hai-dong Fang; Hui Liu; Bin Zhang; Cheng-qiang Shu; Qing-chun Deng; Gang-cai Liu; Qian-qian Yang (Journal of Mountain Science, 2017)

Sodium P-Aminosalicylic Acid Improved Manganese-Induced Learning and Memory Dysfunction via Restoring the Ultrastructural Alterations and γ-Aminobutyric Acid Metabolism Imbalance in the Basal Ganglia - Chao-Yan Ou; Yi-Ni Luo; Sheng-Nan He; Xiang-Fa Deng; Hai-Lan Luo; Zong-Xiang Yuan; Hao-Yang Meng; Yu-Huan Mo; Shao-Jun Li; Yue-Ming Jiang (Biological Trace Element Research, 2017)

Attraction of Coffee Bean Weevil, Araecerus fasciculatus, to Volatiles from the Industrial Yeast Kluyveromyces lactis - Shuai Yang; Xiang-Dong Mei; Xiao-Fang Zhang; Yao-Fa Li; Dongmei She; Tao Zhang; Jun Ning (Journal of Chemical Ecology, 2017)

Effects of short-term inflammatory and/or hypoxic pretreatments on periodontal ligament stem cells: in vitro and in vivo studies - Yang Yu; Chun-Sheng Bi; Rui-Xin Wu; Yuan Yin; Xi-Yu Zhang; Ping-Heng Lan; Fa-Ming Chen (Cell and Tissue Research, 2016)

Emergy assessment of three home courtyard agriculture production systems in Tibet Autonomous Region, China - Fa-chun Guan; Zhi-peng Sha; Yu-yang Zhang; Jun-feng Wang; Chao Wang (Journal of Zhejiang University-SCIENCE B, 2016)

QTL detection for wheat kernel size and quality and the responses of these traits to low nitrogen stress - Fa Cui; Xiaoli Fan; Mei Chen; Na Zhang; Chunhua Zhao; Wei Zhang; Jie Han; Jun Ji; Xueqiang Zhao; Lijuan Yang; Zongwu Zhao; Yiping Tong; et al. (Theoretical and Applied Genetics, 2016)

TLR1 expression in mouse brain was increased in a KA-induced seizure model - Fa-Xiang Wang; Shi-Yong Liu; Xin Zheng; Xin Chen; Lin-Xiang Lu; Bin Chen; Xiao-yi Xiong; Hai-Feng Shu; Qing-Wu Yang; Hui Yang (Inflammation Research, 2015)

Quercetin induces mitochondrial-derived apoptosis via reactive oxygen species-mediated ERK activation in HL-60 leukemia cells and xenograft - Wei-Jiunn Lee; Michael Hsiao; Junn-Liang Chang; Shun-Fa Yang; Tsui-Hwa Tseng; Chao-Wen Cheng; Jyh-Ming Chow; Ke-Hsun Lin; Yung-Wei Lin; Chung-Chi Liu; Liang-Ming Lee; Ming-Hsien Chien (Archives of Toxicology, 2015)

Zinc binds to and directly inhibits protein phosphatase 2A in vitro - Yan Xiong; Dan-Ju Luo; Xiu-Lian Wang; Mei Qiu; Yang Yang; Xiong Yan; Jian-Zhi Wang; Qi-Fa Ye; Rong Liu (Neuroscience Bulletin, 2015)

Alternaria toxin-induced resistance in rose plants against rose aphid (Macrosiphum rosivorum): effect of tenuazonic acid - Fa-zhong Yang; Bin Yang; Bei-bei Li; Chun Xiao (Journal of Zhejiang University-SCIENCE B, 2015)

Genetic polymorphisms of CYP2D6*10 and the effectiveness of combined tamoxifen citrate and testosterone undecanoate treatment in infertile men with idiopathic oligozoospermia - Kai-fa Tang; Yi-li Zhao; Shang-shu Ding; Qi-fei Wu; Xing-yang Wang; Jia-qi Shi; Fa Sun; Jun-ping Xing (Journal of Zhejiang University-SCIENCE B, 2015)

Early-life sleep deprivation persistently depresses melatonin production and bio-energetics of the pineal gland: potential implications for the development of metabolic deficiency - Li-You Chen; Cheng Tiong; Chung-Hung Tsai; Wen-Chieh Liao; Shun-Fa Yang; Su-Chung Youn; Fu-Der Mai; Hung-Ming Chang (Brain Structure and Function, 2015)

Retrieving three-dimensional displacement fields of mining areas from a single InSAR pair - Zhi Wei Li; Ze Fa Yang; Jian Jun Zhu; Jun Hu; Yun Jia Wang; Pei Xian Li; Guo Liang Chen (Journal of Geodesy, 2015)

Alpha-Synuclein Oligomerization in Manganese-Induced Nerve Cell Injury in Brain Slices: A Role of NO-Mediated S-Nitrosylation of Protein Disulfide Isomerase - Bin Xu; Cui-Hong Jin; Yu Deng; Wei Liu; Tian-Yao Yang; Shu Feng; Zhao-Fa Xu (Molecular Neurobiology, 2014)

Paenibacillus abyssi sp. nov., isolated from an abyssal sediment sample from the Indian Ocean - Xiao-Fang Huang; Fa-Zuo Wang; Wei Zhang; Jie Li; Juan Ling; Jian Yang; Jun-De Dong; Xin-Peng Tian (Antonie van Leeuwenhoek, 2014)

Testing hypotheses of mitochondrial gene‐tree paraphyly: unravelling mitochondrial capture of the Streak‐breasted Scimitar Babbler ( P omatorhinus ruficollis ) by the Taiwan Scimitar Babbler ( P omatorhinus musicus ) - Feng Dong; Fa‐Sheng Zou; Fu‐Min Lei; Wei Liang; Shou‐Hsien Li; Xiao‐Jun Yang (Molecular Ecology, 2014)
Species‐level paraphyly inferred from mitochondrial gene trees is a prevalent phenomenon in taxonomy and systematics, but there are several potential causes that are not easily explained by currently used methods. This study aimed to test the underlying causes behind the observed paraphyly of Streak‐breasted Scimitar Babbler ( P omatorhinus ruficollis ) via statistical analyses of four mitochondrial (mt DNA ) and nine nuclear (nu DNA ) genes. Mitochondrial gene trees show paraphyly of P . ruficollis with respect to the Taiwan Scimitar Babbler ( P omatorhinus musicus ), but nuclear genealogies support a sister‐group relationship. Predictive coalescent simulations imply several hypothetical explanations, the most likely being mitochondrial capture of P . ruficollis by P . musicus for the observed cyto‐nuclear incongruence. Further approximate Bayesian computation suggests a unidirectional introgression model with substantial level of gene flow from P . ruficollis to P . musicus during their initial divergence during the Late Pleistocene. This specific observation frames several potential causes for incongruent outcomes of mitochondrial and nuclear introgression in general, and on the whole, our results underscore the strength of multiple independent loci for species delimitation and importance of testing hypotheses that explain disparate causes of mitochondrial gene‐tree paraphyly.

Vitreoscilla hemoglobin promotes Salecan production by Agrobacterium sp. ZX09 - Yun-mei Chen; Hai-yang Xu; Yang Wang; Jian-fa Zhang; Shi-ming Wang (Journal of Zhejiang University-SCIENCE B, 2014)

Hypocalcemia: a reversible cause of T wave alternans and heart failure - Yi-chen Yang; Fa-rong Shen; Yuan-qiang Lu (Journal of Zhejiang University-SCIENCE B, 2014)

Alpha-Synuclein is Involved in Manganese-Induced ER Stress via PERK Signal Pathway in Organotypic Brain Slice Cultures - Bin Xu; Fei Wang; Sheng-Wen Wu; Yu Deng; Wei Liu; Shu Feng; Tian-Yao Yang; Zhao-Fa Xu (Molecular Neurobiology, 2014)

Establishment and characterization of dairy cow growth hormone secreting anterior pituitary cell model - Jian-Fa Wang; Shou-Peng Fu; Su-Nan Li; Zhan-Qing Yang; Wen-Jing Xue; Zhi-Qiang Li; Wei Wang; Ju-Xiong Liu (In Vitro Cellular & Developmental Biology - Animal, 2014)

Accumulation of mercury in rice grain and cabbage grown on representative Chinese soils - Chun-fa Liu; Cheng-xian Wu; Muhammad T. Rafiq; Rukhsanda Aziz; Dan-di Hou; Zhe-li Ding; Zi-wen Lin; Lin-jun Lou; Yuan-yuan Feng; Ting-qiang Li; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

α-Mangostin induces mitochondrial dependent apoptosis in human hepatoma SK-Hep-1 cells through inhibition of p38 MAPK pathway - Shu-Ching Hsieh; Min-Hsien Huang; Chun-Wen Cheng; Jyun-Hao Hung; Shun-Fa Yang; Yi-Hsien Hsieh (Apoptosis, 2013)

Gorham-Stout syndrome in mainland China: a case series of 67 patients and review of the literature - Po Hu; Xiang-gui Yuan; Xin-yang Hu; Fa-rong Shen; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Conditional and unconditional QTL mapping of drought-tolerance-related traits of wheat seedling using two related RIL populations - HONG ZHANG; FA CUI; LIN WANG; JUN LI; ANMING DING; CHUNHUA ZHAO; YINGUANG BAO; QIUPING YANG; HONGGANG WANG (Journal of Genetics, 2013)

Iodine Excess Induces Hepatic Steatosis Through Disturbance of Thyroid Hormone Metabolism Involving Oxidative Stress in BaLB/c Mice - Yun Xia; Wei Qu; Li-Na Zhao; Hao Han; Xue-Feng Yang; Xiu-Fa Sun; Li-Ping Hao; Jian Xu (Biological Trace Element Research, 2013)

Distribution and phenotypic expression of mineralocorticoid receptor and CYP11B2 T-344C polymorphisms in a Taiwanese hypertensive population - Sung-Kien Sia; Hui-Ling Chiou; Shiuan-Chih Chen; Chin-Feng Tsai; Shun-Fa Yang; Kwo-Chang Ueng (Molecular Biology Reports, 2013)

Coexpression of ScNHX1 and ScVP in Transgenic Hybrids Improves Salt and Saline-Alkali Tolerance in Alfalfa (Medicago sativa L.) - Liang Liu; Xiu-Duo Fan; Fa-Wei Wang; Nan Wang; Yuan-Yuan Dong; Xiu-Ming Liu; Jing Yang; Yan-Fang Wang; Hai-Yan Li (Journal of Plant Growth Regulation, 2013)

Phylogenetic diversity of bacterial endophytes of Panax notoginseng with antagonistic characteristics towards pathogens of root-rot disease complex - Li Ma; Yong Hong Cao; Ming Hui Cheng; Ying Huang; Ming He Mo; Yong Wang; Jian Zhong Yang; Fa Xiang Yang (Antonie van Leeuwenhoek, 2013)

A New Elasto-Viscoplastic Damage Model Combined with the Generalized Hoek–Brown Failure Criterion for Bedded Rock Salt and its Application - Lin-jian Ma; Xin-yu Liu; Qin Fang; Hong-fa Xu; Hui-min Xia; Er-bing Li; Shi-gang Yang; Wen-pei Li (Rock Mechanics and Rock Engineering, 2013)

Analysis of genetic diversity in the tuber mustard (Brassica juncea var. tumida Tsen et Lee) in the Yangtze river basin of China - Ping Fang; Fa-Bo Chen; Qi-Lun Yao; Ke-Cheng Yang; Guang-Fan Zhou; Yong-Hong Fan; Zhao-Rong Zhang; Jin-Juan Shen; Hong Zhang (Genetic Resources and Crop Evolution, 2013)

Cathepsin B SNPs elevate the pathological development of oral cancer and raise the susceptibility to carcinogen-mediated oral cancer - Mu-Kuan Chen; Shih-Chi Su; Chiao-Wen Lin; Chiung-Man Tsai; Shun-Fa Yang; Chia-Jui Weng (Human Genetics, 2012)

Over-expression of integrin-linked kinase correlates with aberrant expression of Snail, E-cadherin and N-cadherin in oral squamous cell carcinoma: implications in tumor progression and metastasis - Dan Zhao; Xiu-Fa Tang; Kai Yang; Ji-Yuan Liu; Xiang-Rui Ma (Clinical & Experimental Metastasis, 2012)

Lipocalin-2 Induces Apoptosis in Human Hepatocellular Carcinoma Cells Through Activation of Mitochondria Pathways - Ming-Hsien Chien; Tsung-Ho Ying; Shun-Fa Yang; Ji-Kuen Yu; Chih-Wei Hsu; Shu-Ching Hsieh; Yi-Hsien Hsieh (Cell Biochemistry and Biophysics, 2012)

miR-210 activates notch signaling pathway in angiogenesis induced by cerebral ischemia - Yuan-Lei Lou; Fei Guo; Fen Liu; Fa-Liang Gao; Peng-Qi Zhang; Xin Niu; Shang-Chun Guo; Jun-Hui Yin; Yang Wang; Zhi-Feng Deng (Molecular and Cellular Biochemistry, 2012)

Impact of MCP-1 and CCR-2 gene polymorphisms on coronary artery disease susceptibility - Hsiu-Ling Lin; Kwo-Chang Ueng; Yih-Shou Hsieh; Whei-Ling Chiang; Shun-Fa Yang; Shu-Chen Chu (Molecular Biology Reports, 2012)

VEGF upregulates VEGF receptor-2 on human outer root sheath cells and stimulates proliferation through ERK pathway - Wei Li; Zhong-Fa Lu; Xiao-Yong Man; Chun-Ming Li; Jiong Zhou; Jia-Qi Chen; Xiao-Hong Yang; Xian-Jie Wu; Sui-Qing Cai; Min Zheng (Molecular Biology Reports, 2012)

Study on synthesis of thalidomide analogues and their bioactivities; inhibition on iNOS pathway and cytotoxic effects - Chao-Bin Yeh; Pen-Yuan Lin; Jin-Ming Hwang; Chi-Jung Su; Ying-Tung Yeh; Shun-Fa Yang; Ming-Chih Chou (Medicinal Chemistry Research, 2012)

‘Candidatus Phytoplasma ziziphi’ associated with Sophora japonica witches’ broom disease in China - Zhan-Cui Yu; Yang Cao; Qun Zhang; De-Fa Deng; Zhen-Yu Liu (Journal of General Plant Pathology, 2012)

Arsenic induces apoptosis in myoblasts through a reactive oxygen species-induced endoplasmic reticulum stress and mitochondrial dysfunction pathway - Yuan-Peng Yen; Keh-Sung Tsai; Ya-Wen Chen; Chun-Fa Huang; Rong-Sen Yang; Shing-Hwa Liu (Archives of Toxicology, 2012)

Janibacter alkaliphilus sp. nov., isolated from coral Anthogorgia sp - Jie Li; Li-Juan Long; Ling–Ling Yang; Ying Xu; Fa-Zuo Wang; Qing-Xin Li; Si Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Lysinibacillus mangiferahumi sp. nov., a new bacterium producing nematicidal volatiles - Ling-Ling Yang; Ying Huang; Jie Liu; Li Ma; Ming-He Mo; Wen-Jun Li; Fa-Xiang Yang (Antonie van Leeuwenhoek, 2012)

Erratum to: Fisetin induces apoptosis in human cervical cancer HeLa cells through ERK1/2-mediated activation of caspase-8-/caspase-3-dependent pathway - Tsung-Ho Ying; Shun-Fa Yang; Su-Ju Tsai; Shu-Ching Hsieh; Yi-Chang Huang; Da-Tian Bau; Yi-Hsien Hsieh (Archives of Toxicology, 2012)

Bt rice expressing Cry1Ab does not stimulate an outbreak of its non-target herbivore, Nilaparvata lugens - Yang Chen; Jun-Ce Tian; Wei Wang; Qi Fang; Zunnu Raen Akhtar; Yu-Fa Peng; Hu Cui; Yu-Yuan Guo; Qi-Sheng Song; Gong-Yin Ye (Transgenic Research, 2012)

Alternaria toxin-induced resistance against rose aphids and olfactory response of aphids to toxin-induced volatiles of rose plants - Fa-zhong Yang; Li Li; Bin Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Fisetin induces apoptosis in human cervical cancer HeLa cells through ERK1/2-mediated activation of caspase-8-/caspase-3-dependent pathway - Tsung-Ho Ying; Shun-Fa Yang; Su-Ju Tsai; Shu-Ching Hsieh; Yi-Chang Huang; Da-Tian Bau; Yi-Hsien Hsieh (Archives of Toxicology, 2012)

Significant genetic differentiation between native and introduced silver carp (Hypophthalmichthys molitrix) inferred from mtDNA analysis - Si-Fa Li; Jia-Wei Xu; Qi-Ling Yang; Cheng-Hui Wang; Duane C. Chapman; Guoqing Lu (Environmental Biology of Fishes, 2011)

Effects of temporarily disrupting BBB on activity-induced manganese-dependent functional MRI - Zhiqiang Fa; Run Zhang; Peng Li; Jing Zhang; Peng Zhang; Shaofang Zhu; Qu Wu; Fanheng Huang; Yanping Liu; Lujun Yang; Haigang Chang; Zhibo Wen; et al. (Brain Imaging and Behavior, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

Supplemental Selenium Alleviates the Toxic Effects of Excessive Iodine on Thyroid - Jian Xu; Xiao-Li Liu; Xue-Feng Yang; Huai-Lan Guo; Li-na Zhao; Xiu-Fa Sun (Biological Trace Element Research, 2011)

Leptin expression and leptin receptor gene polymorphisms in growth hormone deficiency patients - Pen-Hua Su; Jia-Yuh Chen; Ju-Shan Yu; Suh-Jen Chen; Shun-Fa Yang (Human Genetics, 2011)

Dwarf apple MbDREB1 enhances plant tolerance to low temperature, drought, and salt stress via both ABA-dependent and ABA-independent pathways - Wei Yang; Xiao-Dan Liu; Xiao-Juan Chi; Chang-Ai Wu; Yan-Ze Li; Li-Li Song; Xiu-Ming Liu; Yan-Fang Wang; Fa-Wei Wang; Chuang Zhang; Yang Liu; Jun-Mei Zong; et al. (Planta, 2011)

Derived vascular endothelial cells induced by mucoepidermoid carcinoma cells: 3-dimensional collagen matrix model - Sen Yang; Li-juan Guo; Qing-hong Gao; Ming Xuan; Ke Tan; Qiang Zhang; Yu-ming Wen; Chang-mei Wang; Xiu-fa Tang; Xiao-yi Wang (Journal of Zhejiang University-SCIENCE B, 2010)

Potential water sources for Late Quaternary Megalake Jilantai-Hetao, China, inferred from mollusk shell 87Sr/86Sr ratios - Yu-Xin Fan; Fa-Hu Chen; Guo-Xiao Wei; David B. Madsen; Charles G. Oviatt; Hui Zhao; Xi Chun; Li-Ping Yang; Tian-Lai Fan; Guo-Qiang Li (Journal of Paleolimnology, 2010)

Calling Behavior and Rhythms of Sex Pheromone Production in the Black Cutworm Moth in China - Yu-yong Xiang; Mao-fa Yang; Zi-zhong Li (Journal of Insect Behavior, 2010)

Intra-population genetic diversity of two wheatgrass species along altitude gradients on the Qinghai-Tibetan Plateau: its implication for conservation and utilization - Xue-Bing Yan; Yu-Xia Guo; Chong Zhao; Fa-Yang Liu; Bao-Rong Lu (Conservation Genetics, 2009)

Short hairpin RNA targeting NP mRNA inhibiting Newcastle disease virus production and other viral structural mRNA transcription - Hua Yue; Shu Deng; Fa-long Yang; Ding-fei Li; An-jing Fu; Fan Yang; Cheng Tang (Virus Genes, 2009)

Growth of Chlorella pyrenoidosa in wastewater from cassava ethanol fermentation - Cong-fa Yang; Zhong-yang Ding; Ke-chang Zhang (World Journal of Microbiology and Biotechnology, 2008)

Eight novel microsatellite markers from the Père David’s deer (Elaphurus davidianus) - Yang Jiao; Yun-Fa Ge; Sheng-Guo Fang (Conservation Genetics, 2008)

Study on ambient air quality in Beijing for the summer 2008 Olympic Games - Wen-xing Wang; Fa-he Chai; Kai Zhang; Shu-lan Wang; Yi-zhen Chen; Xue-zhong Wang; Ya-qin Yang (Air Quality, Atmosphere & Health, 2008)

Protein degradation and nitrogen remobilization during leaf senescence - Juan Liu; Yun Hai Wu; Jun Jie Yang; Yu Dong Liu; Fa Fu Shen (Journal of Plant Biology, 2008)

Berberine induces apoptosis in SW620 human colonic carcinoma cells through generation of reactive oxygen species and activation of JNK/p38 MAPK and FasL - Wen-Hsiu Hsu; Yih-Shou Hsieh; Hsing-Chun Kuo; Chun-Yuh Teng; Hai-I Huang; Chau-Jong Wang; Shun-Fa Yang; Yi-Sheng Liou; Wu-Hsien Kuo (Archives of Toxicology, 2007)

Changes of cell proliferation and differentiation in the developing brain of mouse - Lin Qiu; Chang-Lian Zhu; Xiao-Yang Wang; Fa-Lin Xu (Neuroscience Bulletin, 2007)

Weathering mechanism of the Cretaceous argillaceous siltstone caverns, Longyou, China - Gai-mei Guo; Li-hui Li; Zhi-fa Yang; Bo Tao; Yong-xin Qu; Jian Zheng (Bulletin of Engineering Geology and the Environment, 2005)

The impact of NiO on microstructure and electrical property of solid oxide fuel cell anode - Yan Li; Zhong-yang Luo; Chun-jiang Yu; Dan Luo; Zhu-an Xu; Ke-fa Cen (Journal of Zhejiang University-SCIENCE B, 2005)

Use of fluorometry for determination of skim milk powder adulteration in fresh milk - Rong-fa Guan; Dong-hong Liu; Xing-qian Ye; Kai Yang (Journal of Zhejiang University-SCIENCE B, 2005)

Identification of two chilling-regulated 1-aminocyclopropane- 1-carboxylate synthase genes from citrus (Citrus sinensis Osbeck) fruit - Wai Shing Wong; Wen Ning; Pei Lin Xu; Shain Dow Kung; Shang Fa Yang; Ning Li (Plant Molecular Biology, 1999)

Evaluation of Roegneria for resistance to head scab caused by Fusarium graminearum Schwabe - Wan Yong-Fang; Yen Chi; Yang Jun-Liang; Liu Fa-Quan (Genetic Resources and Crop Evolution, 1997)

Differential induction of seven 1-aminocyclopropane-1-carboxylate synthase genes by elicitor in suspension cultures of tomato (Lycopersicon esculentum) - Jürg H. Oetiker; David C. Olson; Oi Yin Shiu; Shang Fa Yang (Plant Molecular Biology, 1997)

Intraspecific variation in copper susceptibility of the bluegill sunfish - Chu -fa Tsai; Kwei -yang Chang (Archives of Environmental Contamination and Toxicology, 1984)